Sistem Pendukung Keputusan Penentu Merek Handphone Terbaik Daerah Jawa Tengah Menggunakan Logika Fuzzy Tahani - Sugiarto, Triga Agus (MASALIQ, 2025)
Smartphone usage has become increasingly widespread and integral to daily life, with more than 80% of adults in Indonesia using smartphones. The diversity of features and applications available on smartphones, such as high-quality cameras, internet browsing, and social media, makes them a popular choice compared to other electronic devices. However, the wide range of designs, specifications, and prices can make it difficult for potential users to choose a smartphone that meets their needs. To assist in this selection process, a Decision Support System (DSS) based on fuzzy logic Tahani has been developed. This system is designed to provide smartphone recommendations based on several key criteria such as brand, Antutu score, purchase location, camera quality, RAM capacity, and price. With this method, the DSS can handle uncertainty and consider various criteria to deliver recommendations that best match the preferences and needs of individual users.